Pattern and risk factors of birth defects among the newborns: A hospital based study (Journal of Dhaka National Medical College & Hospital, 2015)
Introduction :Birth defects are one of the important causes of perinatal mortality and morbidity.Methods : A cross sectional descriptive study was carried out in In-patient Department of Obstetrics and Gynaecology in Dhaka National Medical College Hospital between January 2008 and December 2008.Objectives : The objectives of the study was to determine the frequency of identifiable birth defects, to observe the types of birth defects found among the newborns and to estimate the risk factors present among the parents of birth defect babies.Results : During this study period 2990 deliveries took place. The frequency of birth defect babies was found 2% (n=60).  Seventy seven percent of the babies were born at term and 23% of them were born prematurely. Babies were born live and still birth 88.33% and 11.67% respectively. Birth defects were predominant in male (55%) than female (45%) babies. Among the mothers 17%, 32% 38% and 13% were of age 35 years (7%), maternal infection (3%), history of previous birth defects babies (3%), Consanguineous marriage (2%) was found as risk factors. Most common system involved was musculoskeletal system (35%), followed by genitourinary system (24%), central nervous system (19%), and face (15%). Birth defect was found in cardio-vascular and gastrointestinal system was 3% and 3% respectively. Functional defect (Down’s syndrome) was found as 2%J.Dhaka National Med. Coll. Hos. 2015; 21 (01): 32-37